1992
DOI: 10.1002/jhrc.1240150211
|View full text |Cite
|
Sign up to set email alerts
|

Linear temperature programmed retention indices of gasoline range hydrocarbons and chlorinated hydrocarbons on cross‐linked polydimethylsiloxane

Abstract: Key Words:Linear temperature programmed retention indices Gasoline range hydrocarbons Chlorinated hydrocarbons Effect of column pressure on retention index SummaryThis paper describes the experimentally determined linear temperature programmed gas chromatographic retention behavior of hundreds of gasoline range hydrocarbons and chlorinated hydrocarbons on a cross-linked 100 9' 0 polydimethylsiloxane stationary phase.The retention indices of additional compounds which were not available as pure standards were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…(5.38) was demonstrated with experimentally found (T Char ,q Char ) pairs for about 200 solutes and two types of stationary phase polymers [11,64,71]. The database was compiled from published thermodynamic data [51][52][53][54][55][56][57][58][59][60][61][62][64][65][66] and from experimental results developed by the software vendor [74]. A large database of thermodynamic parameters of solute-liquid interaction in GC is compiled in commercial Pro ezGC software [73] covering more than 3000 soluteseach in several liquid polymers widely used for making stationary phases in GC columns [74].…”
Section: Fixed Dimensionless Film Thicknessmentioning
confidence: 80%
“…(5.38) was demonstrated with experimentally found (T Char ,q Char ) pairs for about 200 solutes and two types of stationary phase polymers [11,64,71]. The database was compiled from published thermodynamic data [51][52][53][54][55][56][57][58][59][60][61][62][64][65][66] and from experimental results developed by the software vendor [74]. A large database of thermodynamic parameters of solute-liquid interaction in GC is compiled in commercial Pro ezGC software [73] covering more than 3000 soluteseach in several liquid polymers widely used for making stationary phases in GC columns [74].…”
Section: Fixed Dimensionless Film Thicknessmentioning
confidence: 80%
“…1; Table 1). White et al [12] reported that the influence of average linear velocity on PTRIs is reduced for compounds in gasoline that exhibit similar chemical structures to the reference series of retention index. For the FAMEs we investigated, the PTRIs of the saturated esters with the same carbon chain structure as n-alkanes deviated less than the PTRIs of the unsaturated esters (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Pell et al [11] reported that the extent of the decrease differs with the compound, and in some cases, changing the pressure in CPC mode can reverse the elution order, even when the same column temperature program is used. The influence of pressure on PTRIs in CPC mode has been evaluated by White et al [12] and Baaliouamer et al [13]. In CPC mode, the retention time is locked by adjusting the void time, which is achieved by adjusting the column head pressure [14].…”
Section: Introductionmentioning
confidence: 99%
“…When mixture P s were added, the total mass transfer was for contamination (filling both sides before experiments with hexane and analyzing aliquots by GC/ 510 //0 79 mg/cm 2 /min. This is not significantly different from the average P s of the pure isomers, MS), for glove pinholes and leaking (above detection limit permeant concentrations at time zero), 390 //0 250 mg/cm 2 /min, derived by assuming that each isomer contributes equally at the same time for back permeation (analysis of headspace and challenge side for hexane), and for evaporation (Table II) ; log k(C 18 1), logarithm of the capacity factor 15 for Merck LiChrosorb RP-18 column (16 cm 1 5 mm ID) at 1 mL/min of 70 : 30 (w/w) methanol/water using a ultraviolet detector; log k(C 18 2), logarithm of the capacity factor in water 16 for a Perkin Elmer HS-5-C 18 column (12.5 cm 1 4.6 mm ID) at 1.5 mL/min of 50 to 90% acetonitrile/water and 50 to 90% methanol/water mobile phases using a 254 nm detector; log k(GC1), logarithm of the capacity factor 17 on 15% squalene on 80/100 mesh silanized white support (3 m 1 4 mm ID stainless steel column) at 100ЊC at hydrogen carrier gas flow of 80 // 0 0.5 mL/min for a thermal conductivity detector; log k(GC2), logarithm of the capacity factor 18 on Petrocol DH coated (0.5 mm film) fused silica capillary column (100 m 1 0.25 mm ID) at 1Њ/min from 30 to 220ЊC at helium carrier gas flow 31.5 mL/min using a flame ionization detector; DIF, infinite dilution diffusivity 19 (9) are higher. The slightly higher temperature used P s /t l Å 0.0119 D p / 0.786 r Å 0.668 (10) in the present study may explain this, differences in nitrile glove production, or the presence of a ln(P s /t l ) Å 0.00133 D p / 1.05 r Å 0.702 (11) liquid collection medium rather than air.…”
Section: Methodsmentioning
confidence: 99%